The Therapeutic Effects of Dodecaborate Containing Boronophenylalanine for Boron Neutron Capture Therapy in a Rat Brain Tumor Model - Yusuke Fukuo; Yoshihide Hattori; Shinji Kawabata; Hideki Kashiwagi; Takuya Kanemitsu; Koji Takeuchi; Gen Futamura; Ryo Hiramatsu; Tsubasa Watanabe; Naonori Hu; Takushi Takata; Hiroki Tanaka; et al. (Biology, 2020)
Background: The development of effective boron compounds is a major area of research in the study of boron neutron capture therapy (BNCT). We created a novel boron compound, boronophenylalanine–amide alkyl dodecaborate (BADB), for application in BNCT and focused on elucidating how it affected a rat brain tumor model. Methods: The boron concentration of F98 rat glioma cells following exposure to boronophenylalanine (BPA) (which is currently being utilized clinically) and BADB was evaluated, and the biodistributions in F98 glioma-bearing rats were assessed. In neutron irradiation studies, the in vitro cytotoxicity of each boron compound and the in vivo corresponding therapeutic effect were evaluated in terms of survival time. Results: The survival fractions of the groups irradiated with BPA and BADB were not significantly different. BADB administered for 6 h after the termination of convection-enhanced delivery ensured the highest boron concentration in the tumor (45.8 μg B/g). The median survival time in the BADB in combination with BPA group showed a more significant prolongation of survival than that of the BPA group. Conclusion: BADB is a novel boron compound for BNCT that triggers a prolonged survival effect in patients receiving BNCT.